Communication Effectiveness of Facebook Fanpage Tourism Authority of Thailand, Nakhon Si Thammarat by Members’ Viewpoint - แก้วเพ็ง สิรินารถ; มีศิลปวิกกัย กาญจนา (Siam Communication Review, 2018)
The study of “Communication Effectiveness of Facebook Fanpage of Tourism Authority of Thailand Nakhon Si Thammarat by Members’ viewpoint” aims to study behavior of interests in social media of Nakhon Si Thammarat Tourism Authority of Thailand Facebook Page Communication in Fan Pages’ attitude and Effectiveness of Nakhon Si Thammarat Tourism Authority of Thailand Facebook Page Communication in Fan Pages’ attitude. This research studies about survey research by using quantitative research. There are questionnaire to collect data and computer software to analyze. Samples are only males and females fan page. Statistics which use in the research are Descriptive Statistic, Frequency, Percentage, Mean, Standard Deviation, and Inferential Statistic such as Chi-square, t-test, and F-test. According to the study, it found that effectiveness of Nakhon Si Thammarat Tourism Authority of Thailand Facebook Page Communication in Fan Pages’ attitude were in the moderate level. When it was separated in parts, it found that complete part was highest percentage (x ̅ = 3.29). The behavior of interests in social media in 2-3 times per week that spent longest time was 1-10 minutes. Before going to bed was a period of interests in social media by using telephone or smart phone in the most percentage.